2011
DOI: 10.1063/1.3585846
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and analysis of the spectral response for AlGaAs/GaAs HPTs for short wavelength optical communication

Abstract: Detailed spectral response (SR) modeling for heterojunction bipolar phototransistors (HPTs) is presented in this work. All the related physical parameters are taken into account for the resolution of photogenerated excess minority carrier continuity equations in the active layers of the HPT. The layer dependence of the optical flux absorption profile at near-bandgap wavelengths is also investigated and its generalization as a single-exponential has been refuted for HPTs based on GaAs material systems (InGaP-Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The micrograph of fabricated device is given in Figure 1 and the absorption area is 1.75 × 10 3 μm 2 . The detailed experimental set up can be found elsewhere [18]. Both the collector and the base currents saturate at the same level, and the gain in this region is unity.…”
Section: Device Structure and Experimental Setupmentioning
confidence: 99%
“…The micrograph of fabricated device is given in Figure 1 and the absorption area is 1.75 × 10 3 μm 2 . The detailed experimental set up can be found elsewhere [18]. Both the collector and the base currents saturate at the same level, and the gain in this region is unity.…”
Section: Device Structure and Experimental Setupmentioning
confidence: 99%
“…To be more specific, the InP/InGaAs HBTs have been used especially in optoelectronic circuits for 1550 nm fiber optic communications. In such application, HBT proves to be a better choice than other devices such as HEMT and GaAs FETs [13] when implemented as an OEM. This is mainly because it can reduce phase noise after the optical injection matches with the injection of an optical signal which has been previously modulated at the oscillation frequency.…”
Section: Introductionmentioning
confidence: 97%
“…It is a strong competitor of p-i-n and APD due to its inherent gain and absence of excess noise. A number of researchers have reported the characteristics of HPT based on III-V compounds and their alloys [28][29][30][31][32] and group-IV compounds [23][24][25][26][27]. Basu et al [23] have reported their study on HPT based on GeSn, which shows that GeSn based HPT can compete with InGaAs based devices.…”
Section: Introductionmentioning
confidence: 99%